2021
DOI: 10.3390/nu13020371
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Docosahexaenoic Acid Associated to Better Prognoses of Patients with Acute Decompensated Heart Failure with Preserved Ejection Fraction

Abstract: The clinical relevance of polyunsaturated fatty acids (PUFAs) in heart failure remains unclear. The aim of this study was to investigate the association between PUFA levels and the prognosis of patients with heart failure with preserved ejection fraction (HFpEF). This retrospective study included 140 hospitalized patients with acute decompensated HFpEF (median age 84.0 years, 42.9% men). The patients’ nutritional status was assessed, using the geriatric nutritional risk index (GNRI), and their plasma levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Additionally, Matsuo N. et al, 2021, conducted a retrospective single-center cohort study [ 90 ]. The study included 140 hospitalized patients with acute decompensated HFpEF.…”
Section: Heart Failure and Pufasmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Matsuo N. et al, 2021, conducted a retrospective single-center cohort study [ 90 ]. The study included 140 hospitalized patients with acute decompensated HFpEF.…”
Section: Heart Failure and Pufasmentioning
confidence: 99%
“…The obtained data showed that low DHA levels are associated with an increase in all-cause death. This indicates that DHA plasma levels may not only be useful in diagnosis but may also be the target of the therapies administered to such patients [ 90 ].…”
Section: Heart Failure and Pufasmentioning
confidence: 99%
“…If confirmed in clinical settings, EPA could also be considered for the treatment of HFpEF [73] with a biological mechanism meant to be mediated through Ffar4, G protein-coupled receptor for n-3 PUFAs, which is able to block TGFβ1-fibrotic signaling in cultured cardiac fibroblasts, as previously reviewed [74]. Regarding human studies, interestingly and in certain contrast to the expected effects of EPA, in a retrospective single-center cohort study including 140 older patients with HFpEF, lower DHA and dihomo-gamma-linolenic acid levels, but not EPA or arachidonic acid levels, were significantly associated with an increase in all-cause mortality [75]. Moreover, in a multivariate regression analysis, low DHA levels were significantly associated with the incidence of all-cause mortality (HR: 0.16, 95% CI: 0.06-0.44), independently of the geriatric nutritional risk index.…”
Section: Cardiovascular Effects Of N-3 Pufas On (Sub)cellular Levelmentioning
confidence: 93%
“…The causality should be tested in the future RCTs in specific population based on their study [ 12 ]. As also reported in ACS, Matsuo et al [ 13 ] have found that low plasma DHA levels were significantly associated with an increase in all-cause death in patients with acute decompensated heart failure with preserved ejection fraction (HFpEF), independent of nutritional status, in which measurement of plasma DHA levels may be useful in identifying high-risk patients with HFpEF, and supplementation with DHA may be a potential therapeutic target in these patients.…”
mentioning
confidence: 87%